Pengaruh Disiplin Kerja Terhadap Kinerja Guru di MI Al Islam Tempel dan MI Al Ihsan Medari - Aninditya Sri Nugraheni; Ratna Rahmayanti (Jurnal Pendidikan Madrasah, 2016)
The research was quantitative research associative. Associative research is research that aims to determine the relationship of two or more variables. There are two variables in this study, the independent variable is the discipline of work and the dependent variable is the performance of teachers. The population in this study are all teachers and MI MI Al Islam Al Ihsan Medari which amounted to 26 teachers. The method used is direct questionnaire method, where a list of questions given directly and specifically to the teacher. The result of this reasearch that work discipline is very positive and significant impact on teacher performance in MI Al Ihsan Medari. Seen from the t_value (variable X - Y (7.450> 2.262). Of the value of R Square looks massive contribution of 0.686 or 68.9% variable teacher performance can be explained by the variable work discipline, while the rest (100% -68.9% = 31.1%) influenced by other factors not examined.